Changes in physical and mental health are associated with cardiovascular disease incidence in postmenopausal women. (11th February 2019) - Saquib, Nazmus; Brunner, Robert; Desai, Manisha; Kroenke, Candyce; Martin, Lisa W; Daviglus, Martha; Allen, Norrina B; Robinson, Jennifer; Tindle, Hilary; Stefanick, Marcia L
Abstract: Background: physical and mental health are important risk factors for cardiovascular disease (CVD) incidence and death among postmenopausal women. The objective of this study was to assess whether changes in physical and mental health were associated with CVD incidence and death. Methods: in the Women's Health Initiative Observational Study, 48, 906 women (50–79 years) had complete data at baseline on physical and mental health (assessed with Short Form-36) and key covariates. Changes in self-reported physical and mental health were calculated between baseline and year 3. Incident CVD and death between year 3 and end of the study were verified with medical records. Results: over a median 8.2-year follow-up, 2, 319 women developed CVD, and 1, 571 women died, including 361 CVD deaths. Women with continued poor health and those with worsened health had significantly increased risk of CVD incidence, CVD-specific death and all-cause death relative to women with continued good health. Both major and minor declines in physical health were associated with an increased risk of these outcomes relative to women with no change in physical health. Only major declines in mental health were associated with poor prognosis. Conclusions: changes in physical and mental health over 3 years were independently associated with subsequent CVD events.